2008
DOI: 10.1007/s00421-007-0660-z
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort range of a military cold protection glove: database by thermophysiological simulation

Abstract: The thermal insulation properties of a military wet/cold protection glove of the German Bundeswehr were investigated using the thermophysiological simulation device CYBOR with a heated full-scale hand model. The aim of this study was the physiology related and more reliable estimation of a database for the thermal comfort range of the glove in terms of environmental limit temperatures and maximum safe wearing times (limit times). For that purpose the simulation device CYBOR is equipped with a control feature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This finding indicates that the manufacturing of gloves can be similar for both genders. Zimmermann et al (2008) [45] established the criterion that the thermal comfort range of a glove should ensure maintenance of the hand T sk at 15 °C. Moreover, the posterior thigh and leg regions were systematically different, with men having higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that the manufacturing of gloves can be similar for both genders. Zimmermann et al (2008) [45] established the criterion that the thermal comfort range of a glove should ensure maintenance of the hand T sk at 15 °C. Moreover, the posterior thigh and leg regions were systematically different, with men having higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Heat transfer throughout the hand by metabolism, blood perfusion, and conduction between the tissue and heat loss by convection and radiation from the skin were incorporated in the model. An average skin temperature of 15 ℃ of five fingers was used as the critical temperature for loss of dexterity (Heus et al, 1995;Zimmermann et al, 2008). There are considerable differences in skin temperatures among different hand segments (Figure 3), with the little fingertip always has the lowest skin temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory and field studies have shown that performing the same type of manual work in a cold environment is more dangerous than in a warm environment [1]. A mean hand skin temperature of 15 °C is considered to be the lowest acceptable temperature for maintaining sufficient hand manual performance [3,5]. Finger dexterity is more sensitive to cold exposure than manual dexterity [6].…”
Section: Introductionmentioning
confidence: 99%